The Juridical Implications of the Anglo-Iranian Oil Company Case - Brendan F. Brown (Washington University Law Quarterly, 1952)
The Anglo-Iranian oil dispute affords an illustration of the profound influence of legal philosophy upon enactment and judicial decision, despite the appearance of sole reliance upon positive law. It demonstrates how able jurists may appraise and utilize such law differently, depending upon their unexpressed and often subconscious convictions as to the nature of law, the extent of civil authority and the purpose of society, both national and international. The legal positions taken by Iran and Great Britain, the rationale of the order granting interim measures of protection by the International Court of Justice on July 5, 1951, and the attitude of the representatives of the various countries who, considered the resolution presented by Great Britain to the Security Council of the United Nations on September 28, 1951 in furtherance of this order, were all pre-determined by nonarticulated jurisprudential assumptions. It is the purpose of this paper to bring to the surface those ethical controls which determined legislative and judicial behavior, and to evaluate the merits of the underlying normative considerations. It will pass judgment upon the jurisdiction of the International Court of Justice to indicate interim measures of protection, and that of the Security Council to support those measures, but it will not undertake to discuss the justice of the agreement between Great Britain and Iran.
Keywords: International law